NITROGEN INPUT II: PERFORMANCE EVALUATION OF BUFFALO MANURE ON THE PRODUCTION OF NATURAL FISH FOOD AND GROWTH PERFORMANCE OF MAJOR CARPS - K. A. Al- Ghanim; S. Mahboob; H. F. Al-Kahem Al-Balawi; A.S. Al-Akel; F. Al-Misned; Z. Ahmad (Journal of Animal and Plant Sciences, 2015)
Fish growth and yield depend on the organic and inorganic fertilizer and supplementary feed in freshwater fish culture practices. In ponds, the required nutrients for the proper growth of fish are limited because of the nutrient loss in pond sediments. This loss of nutrients in pond ecosystem can be reduced through the addition of fertilizer. Thus the aim of this study was to assess the influence of buffalo manure on the primary productivity, and the net fish yield of major carps for one year in four earthen fish ponds. Catla catla, Labeo rohlita and Cirrhinus mrigala  were stocked with a ratio of 40:30:30 to test the input of buffalo manure and compared with control pond (no buffalo manure). Based on its nitrogen contents (1.02 percent) buffalo manure was applied at a rate of 0.15 g nitrogen / 100 g of fish weight daily. The input of this nitrogen source significantly increased fish weight, fork length and total length. The final an average weight of Catla catla, Labeo rohita and Cirrhinus mrigala in the treated and control pond were recorded as 590.24 ± 1.94, 511.34 ± 2.62 and 391.94 ± 2.12 and 162.19  ± 1.72, 160.08  ± 2.01 and 156.84 g’s ± 1.66, respectively. The plankton productivity; phytoplankton and zooplankton abundance and phytoplankton / zooplankton ratios were significantly different in treated and control ponds. Increase in fish yield and nitrogen incorporation efficiency of fish was found to be correlated with water temperature and plankton productivity in treated and control ponds. The net fish yield of 421.35 and 135.75 kg/pond/year of major carps were secured from buffalo manure treated and control ponds respectively.
Keywords: Warm water fishes; pond fertility; buffalo manure; productivity; fish growth; carp production